Modersmålsinriktad finska i svenskspråkiga skolor i Finland – en debattanalys - Hansell, Katri; Pörn, Michaela; Rebers, Ida (Ainedidaktiikka, 2022)
Syftet med artikeln är att med utgångspunkt i en mediedebatt om modersmålsinriktad finska (mofi) fördjupa förståelsen av olika intressentgruppers syn på mofi-undervisning i svenskspråkiga skolor i Finland. Vi granskar teman som lyfts fram och vilka intressentgrupper som uttalar sig om vilka teman. Materialet består av insändare och redaktionens respons på dem, ledare och artiklar. En innehållsanalys av materialet resulterade i två temaområden – det tvåspråkiga samhället och mofi-undervisningen i skolan. Resultaten visar att det finns en variation i synen på mofi-undervisningens uppdrag. Förutom mofi-undervisningen återspeglar debatten också debattörernas syn på tvåspråkighet på individ- och samhällsnivå samt på språkundervisning mer generellt. Native-level Finnish-language syllabus in Swedish-medium schools in Finland – analysis of a media debate Abstract Based on an analysis of a media debate, this article aims to deepen the understanding of different stakeholders’ views on the education of native-level Finnish-language syllabus (mofi) in Swedish-medium schools in Finland. We scrutinize thematic categories arising from the debate and what stakeholders take part in each of these. The data comprises opinion pieces and responses to them by editorial staff, editorials, and articles. The qualitative content analysis resulted in two thematic categories – the bilingual society and mofi teaching. The results reveal variations in perceptions of the mission of mofi education. Besides mofi education, the debate also reflects on participants’ views on individual and societal bilingualism, as well as language education in general. Keywords: Native-level Finnish-language syllabus, language education, bilingualism, societal debate